Transition‐Metal‐Free Biomolecule‐Based Flexible Asymmetric Supercapacitors. Issue 34 (18th February 2016) - Yang, Yun; Wang, Hua; Hao, Rui; Guo, Lin
Abstract : A transition‐metal‐free asymmetric supercapacitor (ASC) is successfully fabricated based on an earth‐abundant biomass derived redox‐active biomolecule, named lawsone. Such an ASC exhibits comparable or even higher energy densities than most of the recently reported transition‐metal‐based ASCs, and this green ASC generation from renewable resources is promising for addressing current issues of electronic hazard processing, high cost, and unsustainability.